The relationship between interpersonal security and social media dependence: a moderated mediation model - Li, Jinglin; Tan, Jiajia; Zhang, Shang; Wang, Haihong; Yi, Xinfa (Frontiers in Psychiatry, 2025)
BackgroundInterpersonal security is an important psychological factor influencing social media use. However, little is known about the mediating and moderating mechanisms linking Interpersonal security and social media dependence.ObjectiveThe present study explored the mediating role of negative rumination between interpersonal safety and social media dependence, as well as cohort differences in sibling conditions as moderators.MethodsA total of 986 college students were surveyed using a cross-sectional design. Participants completed the Interpersonal Security Questionnaire, the Social Media Dependence Scale, and the Negative Rumination Scale.ResultsThe results showed that a significant interrelationship between interpersonal security, negative rumination, and social media dependence. In addition, the role of negative rumination as a mediator of interpersonal security and social media dependence was supported, and the mediating effects were different between the only-child and non-only-child cohorts.ConclusionsFindings of the study provide a psychological basis for the treatment of social media dependence behavior in college students, with the aim of increasing their interpersonal security and reducing their dependence on social media.